Effect of a combination of butorphanol and detomidine on endoscopic assessment of laryngeal function in Thoroughbred yearlings. (29th March 2022) - Almonte, Hugo; Schumacher, James; Johnson, Christopher R.; Berk, Jeffrey T.; Bell, Rhodes P.
Abstract: Background: To the authors' knowledge, the effect of a combination of butorphanol tartrate and detomidine hydrochloride on the laryngeal function and symmetry of the arytenoid cartilages in young Thoroughbred horses has not been examined. Therefore, this study aimed to examine the effects of administration of butorphanol and detomidine on left‐to‐right rima glottidis ratio (L:R RGR), cross‐sectional area of the rima glottidis (CSARG) and grade of laryngeal function of Thoroughbred yearlings examined endoscopically at rest. Methods: Forty‐six Thoroughbred yearlings underwent laryngeal video endoscopy, at rest, before and after sedation with butorphanol and detomidine. Three clinicians assigned grades of laryngeal function after reviewing the video recordings. The L:R RGR and CSARG were measured at the point of arytenoid cartilages' maximal abduction. Student's t ‐test was used to compare the L:R RGR and CSARG. Cohen's kappa ( κ ) was used to compare the intra‐ and interobserver agreements. Spearman's rank order was used to assess agreement between CSARG and grade of laryngeal function. Results: Sedation had no effect on L:R RGR and CSARG. Mean intraobserver agreement of grade of laryngeal function of unsedated yearlings was 93.1%, and that of sedated yearlings was 92.9%. Mean interobserver agreement of grade of laryngeal function of unsedated yearlings was 92.8%, and that of sedated yearlings was 92.7%. Correlation between CSARG and laryngeal function grade was significant for both groups ( p  < 0.001). Conclusion: Sedating Thoroughbred yearlings with detomidine and butorphanol, before endoscopically examining the larynx, did not significantly affect the grade of laryngeal function.